The Knowledge Exchange–Decision Support Model: application to cancer navigation programs - Howard, A. Fuchsia (Springer Berlin Heidelberg, 2013)
PURPOSE: The Knowledge Exchange–Decision Support (KE-DS) Model provides a framework outlining essential components of knowledge generation and exchange. The purpose of this research was to illustrate how the Model makes explicit the different contextual aspects implicit in the planning and implementation of two cancer navigation programs in Canada. METHODS: The KE-DS Model guided the collection and analysis of interviews with program personnel and narrative data. A qualitative thematic analysis was conducted wherein we compared and contrasted the planning and implementation of these two navigation programs. RESULTS: The planning and implementation of these two programs was conceptualized differently and adapted to meet local contingencies. The KE-DS Model highlighted three factors that influenced program delivery. First, the structure of health services was shaped by the interaction of professionals and services operating in the region, and the existing health services influenced the program’s approach to navigation. Second, while there were similarities in the professional roles and responsibilities of the navigators, these roles and responsibilities also reflected local context in their approaches to patient assessment, referral, education, coordination of services, and advocacy. Third, these two distinct approaches to navigation have responded to the needs of diverse populations being served by improving access to care. CONCLUSIONS: Evidence generated using the KE-DS Model could ensure a more robust and structured approach to the planning and implementation of future navigation programs. The Model prompts users to make explicit the different types of evidence utilized during program planning and implementation. The systematic collection of new information on program implementation using the KE-DS Model in future initiatives will contribute to an improved understanding of the science of knowledge exchange.